Basal Cell Adenoma of the Salivary Gland and Possible Recurrence as Basal Cell Adenocarcinoma in a Black-tailed Prairie Dog (Cynomys ludovicianus). (April 2019) - Ueda, K.; Ueda, A.; Ozaki, K.
Summary: We describe a black-tailed prairie dog ( Cynomys ludovicianus ) with a benign biphasic nodular tumour that recurred as a malignant biphasic tumour at the same site 2 years after resection. Both tumours were biphasic with regard to the glandular epithelium and basal cells and contained little of the mucus, cartilage or fibrous tissue that characterize pleomorphic adenoma and carcinoma ex-pleomorphic adenoma. Both the first and second tumours exhibited histopathological features similar to those exhibited by human basal cell adenoma and adenocarcinoma, respectively. Both were resected and the animal was alive with no recurrence or metastasis at the time of writing, 9 months after the second surgery.